Cathepsin-K is a sensitive immunohistochemical marker for detection of micro-granulomas in hypersensitivity pneumonitis - Reghellin, D.; Poletti, V.; Tomassetti, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Hypersensitivity Pneumonitis (HP) is an interstitial lung disease that occurs upon exposure to a variety of inhaled organic antigens.The presence of small non-caseating granulomas and isolated giant cells is not specific, but is considered a relevant histological feature for HP. The detection of granulomas is widely considered as easy on standard histological stains, but microgranuloma detection can be difficult and/or time consuming, especially in chronic HP cases. Cathepsin K (Cath-K) is a potent cysteine protease expressed at high levels in activated macrophages (osteoclasts, and epithelioid cells in granulomas), but is not expressed in resident macrophages thus representing a promising marker to rapidly detect and quantitatively evaluate microgranulomas in interstitial lung diseases.We analyzed the expression of Cath-K by immunohistochemistry in 22 subacute and chronic HP cases, using semi-quantitative scores. Control samples included normal lung tissue, and a variety of interstitial lung diseases: 3 Wegener’s granulomatosis, 3 sarcoidosis, 3 tuberculosis, 1 berylliosis, 20 idiopathic pulmonary fibrosis (IPF), 2 Langerhans’ cell histiocytosis, 5 nonspecific-interstitial pneumonia (NSIP), 5 cryptogenic organising-pneumonia (COP), 2 Airway-Centered Interstitial Fibrosis (ACIF), 5 desquamative interstitial pneumonia (DIP), 3 respiratory bronchiolitis interstitial lung disease (RB-ILD). Intense expression of Cath-K was demonstrated in epithelioid and giant cells in all cases containing granulomas (HP, sarcoidosis, Wegener’s granulomatosis, berylliosis, tuberculosis). Among HP cases 19/22 (86,3%) contained granulomas that could be semiquantitatively evaluated. In all HP and control cases alveolar macrophages did not express Cath-K, including cases characterised by large collections of alveolar macrophages such as DIP and RB-ILD. Conclusions: Cath-K represents a sensitive and specific marker to detect and quantitate granulomatous reactions in interstitial lung diseases, and is particularly useful in chronic HP cases.